Vitamin D Receptor Signaling Enhances Locomotive Ability in Mice. (January 2015) - Sakai, Sadaoki; Suzuki, Miho; Tashiro, Yoshihito; Tanaka, Keisuke; Takeda, Satoshi; Aizawa, Ken; Hirata, Michinori; Yogo, Kenji; Endo, Koichi
ABSTRACT Bone fractures markedly reduce quality of life and life expectancy in elderly people. Although osteoporosis increases bone fragility, fractures frequently occur in patients with normal bone mineral density. Because most fractures occur on falling, preventing falls is another focus for reducing bone fractures. In this study, we investigated the role of vitamin D receptor (VDR) signaling in locomotive ability. In the rotarod test, physical exercise enhanced locomotive ability of wild‐type (WT) mice by 1.6‐fold, whereas exercise did not enhance locomotive ability of VDR knockout (KO) mice. Compared with WT mice, VDR KO mice had smaller peripheral nerve axonal diameter and disordered AChR morphology on the extensor digitorum longus muscle. Eldecalcitol (ED‐71, ELD), an analog of 1, 25(OH)2D3, administered to rotarod‐trained C57BL/6 mice enhanced locomotor performance compared with vehicle‐treated nontrained mice. The area of AChR cluster on the extensor digitorum longus was greater in ELD‐treated mice than in vehicle‐treated mice. ELD and 1, 25(OH)2D3 enhanced expression of IGF‐1, myelin basic protein, and VDR in rat primary Schwann cells. VDR signaling regulates neuromuscular maintenance and enhances locomotive ability after physical exercise. Further investigation is required, but Schwann cells and the neuromuscular junction are targets of vitamin D3 signaling in locomotive ability. © 2014 American Society for Bone and Mineral Research.